Upaya Dewan Pimpinan Daerah Partai Demokrasi Indonesia Perjuangan dalam Mentransformasikan Nilai-Nilai Pancasila pada Kader - Wibowo, Arif Prasetyo (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2020)
This study discussed the purpose of political education for the Regional Leadership Council of the Indonesian Democratic Party of struggle in West Java Province, the relationship of the party’s platform to the values of Pancasila, and the approaches, methods, and media used by the party in growing Pancasila values to its cadres. This study used a qualitative approach with case studies. Data collection was done through observation, interviews, and documentation. Data analysis used interactive analysis. The results of this study were political education carried out by political parties to their cadres was a process of political socialization to improve the quality of human resources owned by the West Java Demokrasi Indonesia Perjuangan Party Regional Board. The relationship between the party platform and Pancasila values was a process of political education in which cadres were given new knowledge, understanding, and experience in transforming their political values and orientation towards the expected ideal system. The approaches, methods, and media carried out by political parties were carried out through the recruitment of political parties to ensure the sustainability and preservation of political parties.